Clinicopathological Profile of Immunoglobulin A Nephropathy Patients - Sharma, Deepak; Bhusal, Pramod; Maharjan, Chunumila; Ghimire, Madhav (Journal of College of Medical Sciences-Nepal, 2024)
Background Immunoglobulin A nephropathy (IgAN) is the most prevalent glomerulonephritis (GN) in the world. It has variation in presentation among the patients. The aim of the research was to evaluate the clinical and histological characteristics of individuals identified by renal biopsy as having Immunoglobulin-A nephropathy (IgAN). Methods For this retrospective investigation, medical records of patients with biopsy-proven IgAN between January 2021 to July 2024 were evaluated. Results Fifty two patients with primary IgAN fulfilled our requirements for inclusion. The prevalence of affected males was higher (61.5%). The average age was 35.26 ± 10.39 years. Of the patients, 84.5% had hypertension. At presentation, the estimated glomerular filtration rate (eGFR) was 15.8 mL/min/1.73 m2 and the median serum creatinine was 3.58 mg/dL. Mesangial hypercellularity (M1), endocapillary hypercellularity (E1), segmental glomerulosclerosis (S1), tubular atrophy/ interstitial fibrosis (T1/T2), and crescents (C1/C2) were present in 46.2%, 38.5%, 88.5%, 75% and 36.6% of patients respectively. 38.5% and 86.5% of patients, respectively, had hypertensive vasculopathy and thrombotic microangiopathy (TMA). Low eGFR at presentation was significantly correlated with tubular atrophy (T1/T2), hypertensive vasculopathy, and TMA on renal biopsy. Conclusion: Since hypertension was the most frequent clinical manifestation of IgAN, we recommend that patients with hypertension be checked for microscopic dysmorphic hematuria and, if found, have a renal biopsy to confirm an early diagnosis of the condition. The presence of TMA on the renal biopsy and hypertensive vasculopathy along with tubular atrophy (T1/T2) were linked to low eGFR at presentation.